3D printing to innovate biopolymer materials for demanding applications: A review. (June 2021) - Li, N.; Qiao, D.; Zhao, S.; Lin, Q.; Zhang, B.; Xie, F.
Abstract: Biopolymers are widely available, low-/nontoxic, biodegradable, biocompatible, chemically versatile, and inherently functional, making them highly potential for a broad range of applications such as biomedicine, food, textile, and cosmetics. 3D printing (3DP) is capable of fabricating some customized, complex material structures composed of single or multiple material constituents that cannot be achieved by conventional methodologies (e.g. internal structures design); thus, 3DP can greatly expand the application of biopolymer materials. This review presents a comprehensive survey of the latest literature in 3DP technology for materials from biopolymers such as polysaccharides and proteins. The most commonly used 3DP techniques (i.e. inkjet printing, extrusion-based printing, stereolithography, selective laser sintering, and binder jetting) in biomedical and food fields are discussed. Critical factors affecting the quality and accuracy of 3D-printed constructs, including rheological characteristics, printing parameters (e.g. printing rate, and nozzle diameter, movement rate, and height), and post-printing processes (e.g. baking, drying, and crosslinking) are analyzed. The properties and the emerging applications of 3D-printed biopolymer materials in biomedical, food, and even wider applications (e.g. wastewater treatment and sensing) are summarized and evaluated. Finally, challenges and future perspectives are discussed. This review can provide insights into the development of new biopolymer-based inks and new biopolymer-based 3D-printed materials with enhanced properties and functionality. Graphical abstract: Image 1 Highlights: 3D printing produces complex biopolymer structures with multiple constituents. Extrusion 3D printing technique the most popular for biopolymers. 3D-printed object quality and accuracy determined by biopolymer and process. 3D-printed biopolymer materials explored for mainly food and medical applications.